Prevalence and correlates of intimate partner violence towards female students of the University of Ibadan, Nigeria (2014)
Background: In Nigeria, there is paucity of information on the IPV burden and experience among young women in courtship and dating relationships. This study assesses the prevalence and correlates of IPV in female undergraduate and postgraduate students in a tertiary institution. Methods: The study was a cross-sectional survey. A four-stage sampling technique was used to select 1,100 undergraduate and 255 postgraduate female students from the University of Ibadan, Nigeria. Data was collected using a 43-item self-administered structured questionnaire. Descriptive statistics and multivariate analyses were carried out at 0.05 level of significance. Results: The life-time prevalence of IPV was 42.3% (postgraduate: 34.5%, undergraduate: 44.1%; P < 0.05). Lifetime experience of psychological, physical and sexual IPV were 41.8%, 7.9% and 6.6% respectively. Recent experience (within the previous 12 months) of violence was also more frequently reported by respondents who had a previous history of physical (62.5%) (OR = 2.65; 95% CI: 2.02-3.49) and sexual (53.2%) (OR = 1.63; 95% CI:1.12-2.35) violence than respondents who had no such history. Postgraduate (OR = 0.64; 95% CI: 0.46-0.87) and married (OR = 0.53; 95% CI: 0.35-0.78) students were less likely to have experienced IPV than undergraduate and single students respectively. Students who smoked (OR = 2.46; 95% CI: 1.58-3.83); consumed alcohol (OR = 2.36; 95% CI: 1.82- 3.06); and with history of interparental violence (OR = 2.40; 95% CI: 1.88- 3.07) had a higher likelihood of experiencing violence than students who were not exposed to these behaviors. Adverse effects (such as the inability to concentrate) of IPV on academic performance were reported by 10.3% of victims. Conclusion: The prevalence of IPV was high. There is the urgent need for interventions that will reduce vulnerability by addressing modifiable risk factors like smoking and alcohol consumption. Interventions should also encourage seeking health care following violence to reduce its consequences.